Phosphorylation and Dephosphorylation of Tau Protein During Synthetic Torpor - Luppi, Marco; Hitrec, Timna; Di Cristoforo, Alessia; Squarcio, Fabio; Stanzani, Agnese; Occhinegro, Alessandra; Chiavetta, Pierfrancesco; Tupone, Domenico; Zamboni, Giovanni; Amici, Roberto; Cerri, Matteo (Frontiers in Neuroanatomy, 2019)
Tau protein is of primary importance for many physiological processes in neurons, where it affects the dynamics of the microtubule system. When hyperphosphorylated (PP-Tau), Tau monomers detach from microtubules and tend to aggregate firstly in oligomers, and then in neurofibrillary tangles, as it occurs in a group of neurodegenerative disorders named thauopathies. A hypothermia-related accumulation of PP-Tau, which is quickly reversed after the return to normothermia, has been shown to occur in the brain of hibernators during torpor. Since, recently, in our lab, a hypothermic torpor-like condition (synthetic torpor, ST) was pharmacologically induced in the rat, a non-hibernator, the aim of the present work was to assess whether ST can lead to a reversible PP-Tau accumulation in the rat brain. PP-Tau was immunohistochemically assessed by staining for AT8 (phosphorylated Tau) and Tau-1 (non-phosphorylated Tau) in 19 brain structures, which were chosen mostly due to their involvement in the regulation of autonomic and cognitive functions in relation to behavioral states. During ST, AT8 staining was strongly expressed throughout the brain, while Tau-1 staining was reduced compared to control conditions. During the following recovery period, AT8 staining progressively reduced close to zero after 6 h from ST. However, Tau-1 staining remained low even after 38 h from ST. Thus, overall, these results show that ST induced an accumulation of PP-Tau that was, apparently, only partially reversed to normal during the recovery period. While the accumulation of PP-Tau may only depend on the physicochemical characteristics of the enzymes regulating Tau phosphorylation, the reverse process of dephosphorylation should be actively regulated, also in non-hibernators. In conclusion, in this work a reversible and widespread PP-Tau accumulation has been induced through a procedure that leads a non-hibernator to a degree of reversible hypothermia, which is comparable to that observed in hibernators. Therefore, the physiological mechanism involved in this process can sustain an adaptive neuronal response to extreme conditions, which may however lead to neurodegeneration when particular intensities and durations are exceeded.